Disentanglement of Degradation Mechanisms by Analyzing Aging Dynamics of Environmentally Friendly Processed Polymer Solar Cells. Issue 12 (18th June 2020) - Alam, Shahidul; Islam, Md. Moidul; Chowdhury, Shadia; Meitzner, Rico; Kästner, Christian; Schubert, Ulrich S.; Hoppe, Harald
Abstract : Lifecycle assessments suggest preventing halogenated solvents or solvent additives for environmentally friendly polymer solar cells. Thus, the active layers of polymer:fullerene bulk heterojunction solar cells based on poly{[4, 8‐bis‐(2‐ethyl‐hexyl‐thiophene‐5‐yl)‐benzo[1, 2‐b:4, 5‐b0]dithiophene‐2, 6‐diyl]‐alt‐[2‐(20‐ethyl‐hexanoyl)‐thieno[3, 4‐b]thiophen‐4, 6‐diyl]} (PBDTTT‐CT) and the fullerene derivative [6, 6]‐phenyl‐C70‐butyric acid methyl ester (PC70 BM) are cast from m ‐xylene solutions. Ortho‐vanilline is used as a nonhazardous and nontoxic solvent additive. Completed photovoltaic devices are subjected to accelerated laboratory weathering tests. Photovoltaic parameters are periodically obtained from current–voltage recordings of the solar cells twice an hour under well‐defined aging conditions following the International Summit on Organic Photovoltaic Stability (ISOS) protocols. An analysis of aging kinetics reveals the superposition of two individual degradation mechanisms, of which one is assigned to continued intermixing and the other one to the formation of a blocking layer by interfacial segregation. Abstract : The analysis of aging kinetics reveals the superposition of two individual degradation mechanisms. By modeling the combination of a biexponential decay with a complementary error function, one is assigned to continued intermixing and the other one to the formation of magnesium oxide (MgO), which results in initially higher work functions and a final stage of completely blocking contacts.